La configuración ideológica del insularismo en el regionalismo español. El caso de La barraca de Vicente Blasco Ibáñez - Minardi, Adriana (Romanica Silesiana)
This paper aims to study ideological configurations that arise from the effect of insularity in La barraca (belonging to the regionalist novel cycle) by Spanish writer Vicente Blasco Ibáñez. One of the main assumptions of this article is that the island effect is a narrative device which suggests regionalism as a class contradiction but also as a form of resistance against urban culture. The author of this article recognizes three rhetorical strategies employed by Ibáñez: mythemes dislocation, analysis of the effect of the Hegelian master / slave relationship, and the dialectic established between totem and taboo. In conclusion, the author focuses on the concept of politically peripheral nationalism. Key words: regionalism, the bunkhouse, valencian huerta, peripheral nationalism